DIPLOMACY AS A TOOL FOR CONFLICT PREVENTION AND MANAGEMENT - Gligorova, Anita; Sherifi, Qazime; Filipovski, Zoran (International Scientific Journal Vision, 2020)
The European continent and the whole world has been accompanied by civil wars within nations - revolutions, secessionist wars, a numerous conflict between states and different ethnic groups. Meanwhile, because of the conflicts, incomparable economic damage has been caused, suffering, bloodshed, and great loss of human lives. This article highlights the meaning of Preventive Diplomacy in International Relations, the role and importance of preventing conflicts, and their management. Then is elaborated the role, importance of engagement International Organization, Regional Organization, and other mechanisms, including other forms of states engagement in Preventive Diplomacy. In short, the authors emphasized the forms by which the various mechanisms in international relations, achieve the prevention, management of conflicts, and the establishment of peace in the hotbeds of conflicts. In the end, authors mentions the challenges and elements for success which followed preventive diplomacy on conflict prevention.